Noninvasive Assessment of Left Atrial Phasic Function in Patients with Hypertension and Diabetes Using Two‐Dimensional Speckle Tracking and Volumetric Parameters. Issue 6 (20th December 2013) - Liu, Yan; Wang, Ke; Su, Dechun; Cong, Tao; Cheng, Yunpeng; Zhang, Ying; Wu, Jian; Sun, Yinghui; Shang, Zhijuan; Liu, Jinqiu; Zhong, Lei; Zou, Lu; et al.
<x xml:space="preserve">Abstract</x> Objective To evaluate the left atrial phasic function of hypertensive patients with or without coexisting diabetes using two‐dimensional speckle tracking echocardiography (2DSTE)‐based strain and strain rate imaging and volumetric parameters. Methods The study included an isolated hypertension group (HT group) comprising 99 patients, a hypertension and diabetes group (HT + DM group) comprising 65 patients, and 26 age‐matched healthy controls. The 2DSTE‐based strain and strain rate images were studied, and the following parameters were measured: peak left atrial longitudinal strain (LAS‐S), early diastolic (LAS‐E) and late diastolic (LAS‐A) atrial longitudinal strains, and systolic (LASR‐S), early diastolic (LASR‐E) and late diastolic (LASR‐A) strain rates. Results The LAS‐S and LASR‐S were lower in the HT group and the HT + DM group compared with the control group (P < 0.001). The LAS‐E and LASR‐E were lower in the HT group (14.9 ± 5.5% and −1.1 ± 0.4/sec, respectively) than in the control group (22.1 ± 8.3% and −1.7 ± 0.6/sec, respectively) (P < 0.001), and they were further depressed in the HT + DM group (12.3 ± 6.3% and −1.0 ± 0.4/sec, respectively) (P < 0.05). There were no significant differences in LAS‐A or LASR‐A among the 3 groups (P > 0.05). Multivariate regression analysis revealed that HT and DM were independently related to LAS‐E and LASR‐E. Conclusions Hypertension can lead to abnormal left atrial reservoir and conduit functions, and coexisting diabetes can further impair conduit function. 2DSTE‐derived strain and strain rate imaging are sensitive methods for evaluating left atrial phasic function.